Raising Funds for The National Healthcare System: Portuguese Physician’s Perspective - Pereira, Helena (2019)
Since 1976 the Portuguese National Health Service (NHS) is mostly financed by public budget. Financial resources directed towards health care have reached a very high level. In fact, approximately 10% of GDP is devoted to health expenditure, which puts Portugal among the countries with the highest level of health spending within Europe. Urgent intervention is needed, not only to better manage the few resources available, as well as to find other funding sources. The financial crisis turns the need to contain public spending a priority, making urgent the definition of funding strategies for the national health systems sustainability. Objective: In this study we collected the physician’s perspective about the most viable funding sources for the NHS and about the best way to finance the hospital services where they are working.